FACTORS INFLUENCING ASSET POVERTY IN TEACHERS HOUSEHOLDS IN PRIMARY SCHOOLS IN BUKEWA SUB-COUNTY MANAFWA DISTRICT. - NABUNYIRA GLORIA MERCY (My University, 2024)
ABSTRACT The study concentrated on factors influencing asset poverty in teacher’s households in primary schools in Bukewa Sub-County, Manafwa District and it considered a sample size of 80 respondents using a descriptive research design that was bot qualitative and quantitative. The study concluded that that low income is an economic factor that has an effect on asset poverty, that low savings is an economic with an effect on asset poverty, that big household size with a big number of family member’s increases consumption of different resources and this increases household spending thus affecting asset poverty as a factor, that limited access to productive assets is another economic factor with a big effect on asset poverty and lastly findings concluded that low returns on household assets is another economic factor that has a negative effect on asset poverty, that Gender inequality where women have lowered financial on access on asset risk tolerance when compared to men. Findings indicated that most teachers live in rural areas are perceived as bad and have limited access to services and this affects investment decisions in assets, and lastly findings, that most teachers lack access to social capital and this limits their investment decisions, that religious organizations also provide important community services through community organizations which include household asset support strongly, that religious organizations are more likely to access assets for income generating opportunities, that involvement in religious activities may cause higher income. For example, religious people may have access to social networks unavailable to those who attend less frequently. The study also recommended the following: There is need to sensitize the community on the causes and ways of how to prevent asset poverty and lastly that Government should increase on teachers’ salaries such that they are able to meet their daily expenses in order to reduce the challenge of asset poverty.